Persistent detection of Tilapia lake virus in wild tilapia and tinfoil barbs - Abdullah, Azila; Mohd Pazai, Afzan Muntaziana; Mohammad Ridzuan, Mohd Syafiq; Sudirwan, Fahmi; Hashim, Shahidan; Abas, Adnan; Murni, Munira; Roli, Zuraidah; Ramly, Rimatulhana; Nawi, Mohd Firdaus (Veterinary World, 2022)
Background and Aim: One of the emerging viral diseases in freshwater fish is Tilapia lake virus (TiLV), which infects all stages of fish and results in mass mortalities. Previously, a TiLV case was detected in the wild environment in Malaysia that involved tilapia and tinfoil barb. Hence, this study aimed to determine the presence of TiLV in wild tilapia (Oreochromis niloticus) as well as tinfoil barbs (Barbonymus schwanenfeldii) at the similar lake after the initial outbreak in year 2017.